Pendekatan Hukum Progresif terhadap Kebijakan Restorative Justice dalam Sistem Peradilan Pidana - Alkautsar, Raden Adya Untea; Bagas Dewanto; Damar Winata; Muhammad Ardhika Fardhan Kusnadi; Diesta Arya Wicaksono (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research investigates the conceptual relationship between the progressive law theory developed by Satjipto Rahardjo and the restorative justice approach within the framework of Indonesia’s criminal justice system. Progressive law places humans at the core of legal objectives, while restorative justice provides a mechanism of resolution through the participation of offenders, victims, and the community. By applying a normative juridical method, this study evaluates legal concepts, statutory regulations, and scholarly works as the basis for assessing the implementation of restorative justice. The findings reveal that restorative justice represents a practical manifestation of progressive legal principles, although its implementation remains hindered by structural, cultural, and paradigmatic obstacles. The main inhibiting factors include the legalistic tendencies among law enforcement officials, lack of empathy, and a doctrinal orientation in legal education. The study concludes that the effectiveness of restorative justice is largely determined by a transformation of perspectives, reform of legal education, and internalization of progressive values within law enforcement practices. The integration of both approaches provides an opportunity to reform the criminal justice system to become more human-oriented, responsive, and socially restorative.